2002
DOI: 10.1002/gps.682
|View full text |Cite
|
Sign up to set email alerts
|

The meaning of acute confusional state from the perspective of elderly patients

Abstract: The findings indicates that what takes place during the ACS is not nonsense but probably a mix of the patient's life history, their present situation and above all a form of communication concerning their emotional state and inner experiences in this new situation. The findings also indicated that one possible approach to the patients is to confirm and support the patients in narrating their experiences both during the confusion and also after the ACS had ceased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 19 publications
5
58
0
6
Order By: Relevance
“…Our findings are consistent with those of previous studies [11][12][13] done outside the ICU. An important finding from our study is that participants reported feeling that staff did not know if the participants were oriented or not.…”
Section: Discussionsupporting
confidence: 94%
“…Our findings are consistent with those of previous studies [11][12][13] done outside the ICU. An important finding from our study is that participants reported feeling that staff did not know if the participants were oriented or not.…”
Section: Discussionsupporting
confidence: 94%
“…A systematic literature search using the terms delirium in combination with each of mental recall, posttraumatic stress disorders, nurse-patient relations, attitude of health We identified seven qualitative [11][12][13][14][15][16][17] and one semiqualitative [18] studies of patients with delirium (Table 1). Two studies examined the relationship between PTSD and delirium in the intensive care unit (ICU) [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…For some patients, a disinterested perplexity, in which they observe events as through a mist, may be the most common mood experienced [11]. Less commonly, patients report enjoying their experiences during delirium [11,12,16].…”
Section: Emotional Feelingsmentioning
confidence: 98%
See 1 more Smart Citation
“…Det eneste hun visste var at hun var i stor fare -ikke på grunn av kritisk sykdom, men fordi hun trodde at hun ble holdt fanget, omgitt av ondskap og brutalitet. Caroline beskriver typiske symptomer ved postoperativt delirium, dramatiske scener som gir opphav til sterke følelser, frykt og panikk (4,5). Det er som å drømme i våken tilstand, eller som å vaere i et våkent mareritt.…”
Section: Dantes Infernofra Helvete Til Høye Haelerunclassified